2001
DOI: 10.1046/j.1468-1331.2001.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic polyneuropathies in Vest‐Agder, Norway

Abstract: Epidemiological data on chronic polyneuropathies, especially inflammatory types, is limited. The purpose of this study was to examine the spectrum of causes and estimated prevalence of various polyneuropathy types in Vest-Agder, and to examine the clinical features of the Vest-Agder population of chronic inflammatory demyelinating polyneuropathy (CIDP). In Vest-Agder county (population of 155 464), polyneuropathy patients are registered in a database and followed prospectively. We did a measure of the database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
92
4
9

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(116 citation statements)
references
References 27 publications
(31 reference statements)
11
92
4
9
Order By: Relevance
“…Older age groups are more likely to have a chronic progressive course of CIDP, whereas a relapsing-remitting pattern is frequently observed in younger patients [3]. The crude prevalence rate of CIDP in different countries has been reported to range between 0.8 and 7.7 per 100,000 population [4][5][6], and falls in between these extremes (3.58 per 100,000 population) for two North-Western Italian Regions (Piedmont and Valle d'Aosta) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Older age groups are more likely to have a chronic progressive course of CIDP, whereas a relapsing-remitting pattern is frequently observed in younger patients [3]. The crude prevalence rate of CIDP in different countries has been reported to range between 0.8 and 7.7 per 100,000 population [4][5][6], and falls in between these extremes (3.58 per 100,000 population) for two North-Western Italian Regions (Piedmont and Valle d'Aosta) [7].…”
Section: Introductionmentioning
confidence: 99%
“…[9,10]. Perforantne ulceracije su česte, naročito kod senzornih polineuropatija sa sporim razvojem [11]. Intenzitet subjektivnih tegoba najveći je u mirovanju, naročito noću.…”
Section: Discussionunclassified
“…13 Where there is encephalo myelitis there are insufficient data to indicate that oral therapy is not inferior and therefore an intravenous regimen is preferred (see Table 2). 14,15 The outcome following treatment is variable with age, duration of symptoms and severity of meningeal inflammation all influencing recovery. Follow-up of 102 appropriately treated patients in Norway found that 70 per cent had complete resolution of signs four months after treatment, with the remainder showing improvement.…”
Section: Treatment and Outcomementioning
confidence: 99%